Mutual Learning: A Real Way to Cooperate? Evidence of More Equal International Development Cooperatio - Malacarne, Silvia (Italian Sociological Review, 2023)
This contribution forms part of the recent debate on international development cooperation, which has been progressively brought to the fore through several interventions promoted by the United Nations and the Organisation for Economic Co-operation and Development, which have long proposed reflection on the value of cooperation aimed at promoting human development and protecting the fundamental rights of human beings. Within this changing landscape, the article aims to analyse the mutual learning concept emerging in the literature on development cooperation. Through a qualitative study based on the administration of 21 semi-structured interviews, this essay proposes a theoretical-empirical definition of mutual learning and explores two further aspects: the conditions that make it possible and its likely implications in practice. There are currently still very few sociological studies that cover mutual learning among cooperation partners. However, if the concept were investigated both theoretically and empirically, it could bring about a paradigm shift in cooperation that could help overcome the ethnocentric logic of colonial heritage, which sees cooperation exclusively as a means for economic aid transfer, and encourage the use of cooperation as a concrete tool for “doing together”. This would involve different actors who, through working in partnership, could enhance their starting resources and learn from each other.